History of Medicine : a scandalously short introduction - Duffin, Jacalyn (University of Toronto Press, 2010)
Up to date and filled with pithy examples and teaching tools such as a searchable online bibliography, History of Medicine continues to demonstrate the power of historical research to inform current health care practice and enhance cultural understanding